2018
DOI: 10.1002/14651858.cd010578.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Community-based supplementary feeding for food insecure, vulnerable and malnourished populations - an overview of systematic reviews

Abstract: BackgroundSupplementary feeding may help food insecure and vulnerable people by optimising the nutritional value and adequacy of the diet, improving quality of life and improving various health parameters of disadvantaged families. In low‐ and middle‐income countries (LMIC), the problems supplementary feeding aims to address are entangled with poverty and deprivation, the programmes are expensive and delivery is complicated.Objectives1. To summarise the evidence from systematic reviews of supplementary feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 141 publications
(303 reference statements)
0
37
1
Order By: Relevance
“…Contrary to previous findings from a randomized dietary intervention from the 1970s on high-protein supplementation in pregnancy [ 1 ], which has since influenced reviews on this subject and dietary recommendations [ 2 , 3 , 4 , 5 , 6 , 7 ], we found no indications of increased risk of growth restrictions or fetal and neonatal deaths at high protein intakes. High protein intake was modestly associated with risk of preterm delivery.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous findings from a randomized dietary intervention from the 1970s on high-protein supplementation in pregnancy [ 1 ], which has since influenced reviews on this subject and dietary recommendations [ 2 , 3 , 4 , 5 , 6 , 7 ], we found no indications of increased risk of growth restrictions or fetal and neonatal deaths at high protein intakes. High protein intake was modestly associated with risk of preterm delivery.…”
Section: Discussioncontrasting
confidence: 99%
“…As an example, the current WHO recommendations for antenatal care do not recommend high-protein supplementation in undernourished populations [ 3 ]. The results from this trial have also weighted heavily in dietary recommendations for well-nourished populations [ 4 ] and in conclusions of systematic reviews [ 2 , 5 , 6 , 7 ]. In contrast, observational studies in well-nourished populations [ 8 , 9 , 10 ] only reported a modest reduction in fetal growth at high maternal protein intakes.…”
Section: Introductionmentioning
confidence: 99%
“…The authors considered this period to be adequate based on other systematic reviews. Visser and colleagues [20] investigated FI in vulnerable and malnourished populations and also defined a publication period of the past 10 years for the search.…”
Section: Methodsmentioning
confidence: 99%
“…Considering this mechanism, we do no longer understand the shortness of many Th ird World populations as an expression of chronic malnutritionindeed, modern Cochrane Systematic Reviews [31] underline the insignificance of nutrition interventions in these countries ("Considering the current evidence base included, supplementary food eff ects are modest at best"). We understand the absence of secular height trends in these populations as an expression of persistent feelings of being inferior.…”
Section: Andmentioning
confidence: 99%